Risk attitudes and well-being in Latin America - Juan Camilo Cardenas; Jeffrey Carpenter (Institute for the Study of Labor (IZA), 2010)
A common premise in both the theoretical and policy literatures on development is that people remain poor because they are too impatient to save and too risk averse to take the sort of chances needed to accumulate wealth. The empirical literature, however, suggests that this assumption is far from proven. We report on field experiments designed to address many of the issues confounding previous analyses of the links between risk preferences and well-being. Our sample includes more than 3,000 participants who were drawn representatively from six Latin American cities: Bogotá, Buenos Aires, Caracas, Lima, Montevideo, San José. In addition to the experiment which reveals interesting cross-country differences, participants completed an extensive survey that provides data on a variety of well-being indicators and a number of important controls. Focusing on risk preferences, we find little evidence of robust links between risk aversion and well-being. However, when we analyze the results of three treatments designed to better reflect common choices made under uncertainty, we see that these, more subtle, instruments correlate better with wellbeing, even after controlling for a variety of other important factors like the accumulation of human capital and access to credit.
Keywords: C91; C93; D03; D81; O12; 330; risk aversion; ambiguity aversion; loss aversion; risk pooling; well-being; Latin America